Static Analysis of Stretching and Strengthening Exercises on Balance and Strength in the Elderly: Literature Review - wijianto, wijianto; Hidayatullah, Muhammad Furqon; Riyadi, Slamet; Bramastia, Bramastia (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: The literature review study is motivated by the presence of physiological changes indicating a decline in balance and strength in the elderly, considering gender differences. This is attributed to the overall decline in various body systems, including balance and muscle strength, in the elderly. The decrease in muscle quality or strength in the elderly has implications for mobility. Methods: The literature review method was applied to five articles obtained from several databases, namely EBSCO, PubMed, and Springer Link. The search keywords for articles included stretching exercise, elderly balance, elderly strength, and resisted exercise for the elderly. The researcher used "AND" as the Boolean operator. Results: The findings of the literature review indicate that both static and dynamic stretching models, combined with resisted exercise for the lower extremities, have an impact on the balance and strength of the elderly, considering gender differences. Conclusion: The review articles revealed: 1) clinical physiological improvements; 2) increased strength in the elderly, and 3) enhanced balance in the elderly. The literature review results demonstrate an improvement in the balance